The Development Project-Based Learning Pedagogical Module for CNC EDM Die Sinking for Machining Industry Program - Fadzil, Muhammad Noorfarhan; Ahmad, Zanariah (Research and Innovation in Technical and Vocational Education and Training, 2022)
This CNC EDM Die Sinking machine is a learning topic for the Industrial Machining Technology course to obtain SKM level two certification. Project-Based Learning (PjBL) can overcome the problem of lack of skills in operating machines because it can actively involve students. This study aims to develop a module for Project-Based Learning (PjBL) of CNC EDM Die Sinking for Industrial Machining Technology program. Module development study design using SIDEK model which is divided into 3 main phases namely needs analysis phase, development design phase and evaluation phase as the main guide for module development. Next, this module develops RPH which contains two projects using project-based learning strategies from the model Adria Steinberg (1998) which contains six principles namely validity, academic accuracy, application of learning, active exploration, adult relationships and assessment. The content evaluation of this module is divided into four parts namely format appropriateness, RPH content for two projects, teaching aids and evaluation rubrics and evaluated by two experts in CNC EDM Die Sinking machining skills and a Project-Based Learning (PjBL) expert. Data were analyzed using descriptive score value for each aspect of content validity assessment consisting of 4 main items. In conclusion, the results of the evaluation showed that the EDM Die Sinking module obtained a high validity value for each item with a value (3.72) for the format appropriateness item, (3.80) for the appropriateness of module content item, (3.83) for the suitability of teaching aids item and (3.73) for the appropriateness of assessment rubrics item. The contribution of this study is to assist the teaching staff in carrying out the process of teaching the topic of EDM Die Sinking machine. This study is expected to provide guidance to instructors in carrying out the process of teaching the topic of EDM Die Sinking machines using project-based learning strategies.